Structural transformation and inclusive growth in Ghana - Robert Darko Osei; Richmond Atta-Ankomah; Monica Lambon-Quayefio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This study examines the structural transformation-inclusive growth nexus for Ghana. The data cover the post-independence period for Ghana and are phased into three periods: the post-independence period to the start of the economic recovery programme (ERP) and structural adjustment programme (SAP) (1957-83), the ERP/SAP period to the start of oil production (1984-2010), and the start of oil production to date (2010-17). The paper finds that structural transformation has been generally weak and also associated with limited inclusive growth. In part, the legacy problem relating to political settlements, and with its roots in the immediate post-independence policies, has been important in shaping these outcomes. The paper concludes by noting that there is potential for the country to move to a path where structural transformation will be more impactful for inclusive growth. However, the risk of adverse political settlements still mitigating this potential impact remains.
Keywords: I32; O14; O47; 330; Ghana; inclusive growth; structural transformation; industrialization